Antiviral Constituents from the Bulbs of Lilium lancifolium - Zhou, Zhong-Liu; Lin, San-Qing; Yang, Hong-Yan; Zhang, Hua-Lin; Xia, Jing-Min (Asian Journal of Chemistry, 2014)
A bioassay-guided fractionation of a methanolic extract of the bulbs of Lilium lancifolium led to the isolation of seven phenolic compounds (1-7) for the first time. Their chemical structures were elucidated on the basis of UV, IR, MS, NMR spectroscopic analyses. All compounds were tested for antiviral activity against respiratory syncytial virus. Compounds 6 and 7 showed significant antiviral activity against respiratory syncytial virus with IC50 values of 9.7 and 7.4 μg/mL and selective index values of 14.9 and 24, respectively.